The royalist army in the first civil war - Roy, I (1963)
The army under discussion is that which was directly under Charles I's command, and was based at Oxford during the war, not the forces stationed permanently in the North or West. This army, the chief strength of the Royalists, was raised in the Midlands in the summer of 1642, by loyal nobility and gentry, who recruited volunteer regiments in the counties where their "interest" was greatest. Attempts to use the existing militia system were largely unsuccessful at this stage of rhe war. The prospect before the King at first seemed unhopeful, but improved as arms from the continent, private financial contributions and Welsh recruits reached him; the army at Edgehill was strong in infantry and was well-paid, but was short of personal weapons. The Council of War became the chief executive and administrative committee for the organisation of the army. The King presided at its meetings, which dealt with a wide range of topics. The papers of the secretary-at-war, Edward Walker, help us to see it at work. Civilian and military elements were combined in the Council, and its mixed character allowed it to act successfully as a mediator in disputes between army units and the civilian population. Subcommittees of the Council were charged with specialist tasks. Other committees were set up at Oxford. The defence of the city, in the absence of the King and the field army during the summer campaigns, was in the hands of a body known as the “Lords Commissioners". In 1644 the King summoned a counter-Parliament to Oxford, and this assembly, and the committee of its members it left behind when it was not in session, played some part in decision-taking. Continued in thesis ...